Instrumental activities of daily living function and cognitive status among Chinese older adults: a serial multiple mediation model - Huang, Sijie; Zhong, Wenjuan; Cheng, Qingzhou; Shuai, Yuxi; Zhu, Jiahui; Diao, Jiawei (Frontiers in Public Health, 2024)
Objective: This study aims to develop and validate a serial multiple mediation model to investigate t he association between IADL(Instrumental Activities of Daily Living) function and cognitive status a mong older adults while exploring the underlying mechanisms. Methods: This cross-sectional study involved 3665 individuals aged 60 years and above who participated in CHARLS (China Health and Retirement Longitudinal Survey). A serial multiple mediation model was utilized to explore the direc t and indirect relationship between IADL function and cognitive status, and whether sleep duration, s ocial engagement and depressive symptoms mediated this relationship. Results: Decreased IADL fun ction was associated with worse cognitive status [effect=-0.620, 95%CI:(-0.692, -0.540)]. Sleep durat ion, SP (social participation), and depressive symptoms all acted as mediators in the relationship bet ween IADL function and cognitive status. Conclusions: This study found both direct and indirect as sociations between IADL function and cognitive status, providing new insights into the effective prev ention and intervention of cognitive decline among older adults.